2013
DOI: 10.5546/aap.2013.22
|View full text |Cite
|
Sign up to set email alerts
|

Sedación y analgesia para procedimientos invasivos en los niños

Abstract: Sedación y analgesia para procedimientos invasivos en los niños Sedation and analgesia in children undergoing invasives procedures RESUMENIntroducción. Producto del aumento de los procedimientos pediátricos, tanto diagnósticos como terapéuticos fuera del quirófano, la sedación y analgesia en este contexto ha cobrado importancia. Objetivo. Caracterizar el tipo de sedoanalgesia utilizada por un equipo de sedación pediátrico en procedimientos fuera del quirófano, así como sus resultados y su seguridad. Pacientes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Therefore, additional doses of ketamine are preferred. In some previous studies with midazolam and ketamine the incidence of oxygen desaturation was between 4.8% and 12%, whereas Ozdemir et al reported no oxygen desaturation [ 7 , 13 , 14 , 15 , 16 ]. In the present study none of the patients’ oxygen saturation dropped below 90%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, additional doses of ketamine are preferred. In some previous studies with midazolam and ketamine the incidence of oxygen desaturation was between 4.8% and 12%, whereas Ozdemir et al reported no oxygen desaturation [ 7 , 13 , 14 , 15 , 16 ]. In the present study none of the patients’ oxygen saturation dropped below 90%.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study none of the patients’ oxygen saturation dropped below 90%. Compared to propofol, the combination of ketamine and midazolam was associated with less hypoxemia [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our institution, ketamine in combination with midazolam was chosen to induce anesthesia in majority of operations according to some literatures that have shown that this combination has a low rate of complication and a shorter recovery time (10,11). In 140 of operations this combination was enough to obtain deep sedation.…”
Section: Discussionmentioning
confidence: 99%
“…52 Para los procedimientos invasivos de corta duración, las drogas de elección son la ketamina y el midazolam. 49,50,53 El propofol se prefiere en los procedimientos cortos para los pacientes que requieren evaluación neurológica frecuente, como pacientes con TEC o en estado convulsivo. 46,50 Sin embargo, existe cada vez más evidencia de que infusiones prolongadas no conllevan efectos adversos.…”
Section: Sedación Analgesia Y Bloqueantes Neuromuscularesunclassified